Nest insulation and incubation constancy of arctic geese - Thompson, Steven C; Raveling, Dennis G (Wildfowl, 1988)
Nest structure and the average proportion of time spent on nests by incubating geese on the Yukon-Kuskokwim Delta, Alaska, varies as follows: Black Brant Branta bernicla nigricans - profuse down and feathers with little vegetation, and 89.9% attentive; Cackling Canada Geese B. canadensis minima - abundant down mixed with vegetation, and 93.6% attentive; Emperor Goose Anser canagicus - sparse down and mostly vegetation, and 99.5% attentive. The cooling of eggs in the nests of these species under 'calm' and 'windy' conditions was monitored in a coldroom. Eggs in Brant nests under windy conditions cooled significantly less than those in Emperor or Cackling Goose nests. The larger and more numerous eggs of Emperor Geese cooled significantly less, but this is of lesser importance than incubation constancy. The amount of insulation in a goose nest seems primarily the result of counteracting selection between the degree of egg cooling associated with incubation constancy, and the minimisation of avian predation on eggs through nest crypticity. The colonial nesting of Brant and attendance by males provide additional defence against avian egg predators.